An introduction of Krill Herd algorithm for engineering optimization - Gandomi, Amir H.; Alavi, Amir H. (Journal of Civil Engineering and Management, 2016)
A new metaheuristic optimization algorithm, called Krill Herd (KH), has been recently proposed by Gandomi and Alavi (2012). In this study, KH is introduced for solving engineering optimization problems. For more verification, KH is applied to six design problems reported in the literature. Further, the performance of the KH algorithm is compared with that of various algorithms representative of the state-of-the-art in the area. The comparisons show that the results obtained by KH are better than the best solutions obtained by the existing methods.First published online: 25 Aug 2015